Epithelial‐to‐mesenchymal transition as a learning paradigm of cell biology. (30th November 2022) - Carvalho Leão, Marnie Hillary; Costa, Manoel Luis; Mermelstein, Claudia
Abstract: Epithelial‐to‐mesenchymal transition (EMT) is a complex biological process that occurs during normal embryogenesis and in certain pathological conditions, particularly in cancer. EMT can be viewed as a cell biology‐based process, since it involves all the cellular components, including the plasma membrane, cytoskeleton and extracellular matrix, endoplasmic reticulum, Golgi apparatus, lysosomes, and mitochondria, as well as cellular processes, such as regulation of gene expression and cell cycle, adhesion, migration, signaling, differentiation, and death. Therefore, we propose that EMT could be used to motivate undergraduate medical students to learn and understand cell biology. Here, we describe and discuss the involvement of each cellular component and process during EMT. To investigate the density with which different cell biology concepts are used in EMT research, we apply a bibliometric approach. The most frequent cell biology topics in EMT studies were regulation of gene expression, cell signaling, cell cycle, cell adhesion, cell death, cell differentiation, and cell migration. Finally, we suggest that the study of EMT could be incorporated into undergraduate disciplines to improve cell biology understanding among premedical, medical and biomedical students.